Analysis Quality of Water River and Quality of Well Water in The Surrounding of Rejo Agung Baru Sugar Factory Madiun - Susanti Oktavia Ningrum (Universitas Airlangga, 2018)
The quality of wastewater sugar factory produced will affect the environmental health quality around the factory. The study aimed to analyze the quality of water river and the quality of wells around the Rejo Agung Baru sugar factory in the Madiun. This study is an descriptive observational. The samples comprised of 5 sampels of water rivers and 7 samples of well water. The results of the study at the quality of water river showed that there are parameters (BOD5 and temperature) unqualified with the quality standards based on the East Java Regional Regulation No. 2 of 2008 about Water Quality Management and Water Pollution Control in the East Java, the quality of water river is also affected by the waste water, trash, agricultural waste, and other pollutants. The result of measuring the quality of water well showed that there are parameters (organic substance) unqualified with quality standards based on Permenkes No: 416/Menkes/PER/ IX/1990 about the Terms and Water Quality Monitoring, the quality of Well water is also affected by the quality of water river, a distance of toilet, domestic wastewater and other pollutants. The quality of water river and the quality of well water have decreased that required supervision on the quality of a river water and the quality of water of a well.